Fashion’s future: the power of biomaterials and digital manufacturing for systemic sustainability - Michela Musto (Techne, 2025)
In an era where fashion mirrors the excesses of a society driven by disposability, the garment emerges as a transformative device to reimagine our relationship with identity, technology, and the environment. This paper delves into the transformative potential of biomaterials and digital manufacturing in redefining fashion as a sustainable and ethical practice. Situated within the post-Anthropocene discourse, the analysis interrogates the environmental and social implications of these innovations, weaving together theoretical perspectives and exemplary case studies that illuminate the convergence of living matter and additive technologies as a space for new ontologies and aesthetic possibilities. The paper critically addresses the existing barriers, which hinder widespread adoption advocating for a systemic model that integrates innovation, ethics, and environmental consciousness.